2017
DOI: 10.1073/pnas.1617035114
|View full text |Cite
|
Sign up to set email alerts
|

Structural hierarchy controlling dimerization and target DNA recognition in the AHR transcriptional complex

Abstract: The aryl hydrocarbon receptor (AHR) belongs to the PAS (PER-ARNT-SIM) family transcription factors and mediates broad responses to numerous environmental pollutants and cellular metabolites, modulating diverse biological processes from adaptive metabolism, acute toxicity, to normal physiology of vascular and immune systems. The AHR forms a transcriptionally active heterodimer with ARNT (AHR nuclear translocator), which recognizes the dioxin response element (DRE) in the promoter of downstream genes. We determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 56 publications
7
62
0
Order By: Relevance
“…To explore the structural basis for this potential communication between the PAS and bHLH domains, Seok et al (1) explored the importance of interdomain interactions observed in their structure. Notably, perturbation of the bHLH-PAS-A interface in AHR appears to disconnect ligand binding from exposure of the nuclear localization signal, allowing for constitutive nuclear localization independent of ligand binding in vivo (1). This finding suggests that allosteric channels between these domains in AHR are important for ligand sensing and nuclear localization.…”
Section: O M M E N T a R Ymentioning
confidence: 97%
See 3 more Smart Citations
“…To explore the structural basis for this potential communication between the PAS and bHLH domains, Seok et al (1) explored the importance of interdomain interactions observed in their structure. Notably, perturbation of the bHLH-PAS-A interface in AHR appears to disconnect ligand binding from exposure of the nuclear localization signal, allowing for constitutive nuclear localization independent of ligand binding in vivo (1). This finding suggests that allosteric channels between these domains in AHR are important for ligand sensing and nuclear localization.…”
Section: O M M E N T a R Ymentioning
confidence: 97%
“…A careful analysis of PAS domains in CLOCK, BMAL1, NPAS1, NPAS3, ARNT, HIF1-α, and HIF2-α identified potential ligand-binding pockets in both PAS-A and PAS-B domains, suggesting the broad potential for ligand binding in these transcription factors (4). Advances in the structural biology of a native, ligand-binding bHLH-PAS complex, AHR-ARNT, by Seok et al (1) brings us one step closer to understanding native ligand binding by PAS domains and highlights the potential for discovery of ligands that similarly regulate other bHLH-PAS transcription factors.…”
Section: O M M E N T a R Ymentioning
confidence: 99%
See 2 more Smart Citations
“…TCDD-AHR complex translocates into the nucleus and binds with aryl hydrocarbon receptor nuclear translocator (ARNT). The AHR/ARNT heterodimer serves as a DNA-binding transcription factor that binds to dioxin-response elements (DREs) in the promoter region and drives the expression of target genes (16).…”
mentioning
confidence: 99%